2017
DOI: 10.1080/00224499.2017.1298714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations and Future Plans After Casual Sexual Experiences: Differences Across Partner Type

Abstract: Casual sexual relationships and experiences (CSREs) are common among emerging adults, and their diversity may contribute to variability in their associations with mental health and future romantic relationship development. The present research used multiple regression analyses to examine how CSRE type (casual dating, friends with benefits [FWB], or booty call/one-night stand) is associated with short-term outcomes of these experiences, including positive and negative evaluations, plans to start a romantic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…In each study where authors tested the difference between positive and negative feelings, participants reported significantly more positive than negative feelings (Campbell, 2008;Owen & Fincham, 2011a, 2011b. In each study that measured positive and negative feelings but did not statistically test for differences, the means of positive feelings were higher than means of negative feelings (Fielder & Carey, 201a;Owen et al, 2011;Snapp et al, 2015;Wesche et al, 2018;Woerner & Abbey, 2017). Furthermore, in each study that assessed scale scores of subjective emotional reactions, the average response was higher than the scale midpoint for positive reactions and lower than the scale midpoint for negative reactions (Eshbaugh & Gute, 2008;Fielder & Carey, 2010a;Gusarova et al, 2012;Kennair et al, 2016Kennair et al, , 2018Lyons et al, 2014;Lewis et al, 2012;Owen & Fincham, 2011a, 2011bWesche et al, 2018).…”
Section: Subjective Emotional Reactionsmentioning
confidence: 99%
“…In each study where authors tested the difference between positive and negative feelings, participants reported significantly more positive than negative feelings (Campbell, 2008;Owen & Fincham, 2011a, 2011b. In each study that measured positive and negative feelings but did not statistically test for differences, the means of positive feelings were higher than means of negative feelings (Fielder & Carey, 201a;Owen et al, 2011;Snapp et al, 2015;Wesche et al, 2018;Woerner & Abbey, 2017). Furthermore, in each study that assessed scale scores of subjective emotional reactions, the average response was higher than the scale midpoint for positive reactions and lower than the scale midpoint for negative reactions (Eshbaugh & Gute, 2008;Fielder & Carey, 2010a;Gusarova et al, 2012;Kennair et al, 2016Kennair et al, , 2018Lyons et al, 2014;Lewis et al, 2012;Owen & Fincham, 2011a, 2011bWesche et al, 2018).…”
Section: Subjective Emotional Reactionsmentioning
confidence: 99%
“…By definition, a booty call involves contacting a non-long-term mate with the primary purpose of engaging in sexual activity. This contact is most commonly made via telephone (Jonason et al, 2009) or by text message (Wentland & Reissing, 2011). Spontaneous contact is considered to be a key feature of the booty-call relationship.…”
Section: The Nature Of Booty-call Relationshipsmentioning
confidence: 99%
“…According to this premise, it consists of sexual encounters with lower investment than a committed relationship (and is thus appealing to men) but has an element of commitment greater than that of a one-time sexual encounter (and is thus appealing to women). Wentland and Reissing (2011) reported that individuals engaged in a booty call do not consider the other party a friend (and, as such, differs from the friends with benefits relationship) and thus do not socialize with one another (see also Jonason et al, 2011). Further, Wentland and Reissing (2011) reported that the booty call does not involve emotional investment and is characterized by an "unemotional, perfunctory manner" (p. 87).…”
Section: The Nature Of Booty-call Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pioneering studies have begun to examine the characteristics, qualities, evaluations, and outcomes of-either expected or actual-sexual behaviors within adolescents' and young adults' romantic relationships (e.g., Choukas-Bradley et al, 2015;Heinrichs et al, 2009;O'Sullivan et al, 2007;Soller, 2014;Widman et al, 2006). Yet, we currently specifically observe a gap in the literature regarding how the previously described conceptual differences between different types of youths' sexual partnerships (e.g., romantic versus casual) may in turn be related to differences in evaluative aspects, like satisfaction, as well as perceptions and behaviors related to sexual health (for exceptions, see: Higgins et al, 2011;McCarthy & Grodsky, 2011;Pedersen & Blekesaune, 2003;Wesche et al, 2017).…”
mentioning
confidence: 99%